SISTEM MONITORING DAN KENDALI SUHU RUANGAN BUDIDAYA JAMUR TIRAM BERBASISINTERNET OF THINGS (Elkom: Jurnal Elektronika dan Komputer, 2025)
The process of cultivating oyster mushrooms is very dependent on the stability of environmental conditions, especially room temperature and humidity, which farmers must pay attention to.  This becomes a problem when the environmental monitoring and control process is carried out manually, requiring a lot of energy and quite a lot of time. This research aims to design a system for monitoring and controlling the room temperature for oyster mushroom cultivation automatically and remotely based on Internet of Things (IoT) technology for farmers. In this system process, this research utilizes the DHT11 temperature and humidity sensor as input, the Arduino Uno microcontroller as a data processor, and the ESP8266 module as a wireless data sender to a Blynk-based Android application.  The development method used in this research is the Software Development Life Cycle (SDLC) waterfall model, and analyzing needs, system design, implementation, testing, and maintenance. Test results show that the system is able to read the temperature and activate the blower (fan) automatically when the temperature exceeds the threshold, as well as displaying temperature data and fan status in real-time via the Blynk application. With this system, monitoring and controlling the mushroom cultivation environment can be carried out more efficiently and flexibly and support optimal cultivation productivity.